Effects of mixed Aqueous-Organic solveuts on the rate of intramolecular Carboxylic Group-Catalyzed cleavage Of N-(4'-Methoxyphenyl)-Phthalamic Acid - Ariffin, Azhar; Khan, M.N.; Leng, S.Y. (2004)
Kinetic study on the cleavage of N-(4'-methoxyphenyl)phthalamic acid (NMPPAH) in mixed H2O-CH3CN and H2O-1,4-dioxan solvents containing 0.05 M HCl reveals the formation of phthalic anhydride (PAn)/phthalic acid (PA) as the sole or major product. Pseudo first-order rate constants (k(1)) for the conversion of NMPPAH to PAn decrease nonlinearly from 60.4 x 10(-5) to 2.64 x 10(-5) s(-1) with the increase in the contents of 1,4-dioxan from 10 to 80% v/v in mixed aqueous solvents. The rate of cleavage of NMPPAH in mixed H2OCH3CN solvents at greater than or equal to 50% v/v CH3CN follows an irreversible consecutive reaction path: NMPPAH k(1) --> PAn k(2) --> PA. The values of k(1) are larger in H2O-CH3CN than in H2O-1,4-dioxan solvents. (C) 2004 Wiley Periodicals, Inc.